Papers and citizenships - Rodrigo, Federico (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2021)
In this work we seek to address the question about the effects of authority that the State produces in different social processes, from focusing on the productivity of the documentations. Our central argument is that certifications (especially DNIs, but also property titles, tax receipts, among others) are a fundamental element of citizen positioning, but in a way that is not necessarily intended institutionally. Taking field experiences in different conflicts carried out by Bolivian migrants -and their associations- in the city of La Plata, we observe that while on the one hand the documentations operate as fundamental cleavages of social dynamics, on the other, their appropriation - and, in certain circumstances, its rejection- is part of the production of unexpected and alternatives citizenships to official parameters. In this way, by adopting and, at the same time stressing the parameters of state authority supported by the documents, migrants make a paradoxical use of them.